Barriers to timely diagnosis and treatment for children with hearing impairment in a southern Indian city: a qualitative study of parents and clinic staff. (3rd October 2017) - Merugumala, Sri Vamshi; Pothula, Vijay; Cooper, Max
Abstract: Objective : In low income countries, deaf children are identified late due to the absence of a universal screening. Hearing impairment is a common yet neglected disability in India that leads to loss of speech and language. This qualitative study explored barriers to accessing appropriate hearing services in one city in southern India. Design : To identify the barriers in timely management of deafness, 25 semi-structured interviews were conducted. Data were examined using Applied Thematic Analysis. Study sample : Seventeen mothers of deaf children, primarily from low socioeconomic backgrounds, and eight staff members at a charitable hearing centre in Hyderabad. Results: Barriers to accessing hearing services included failure to recognise deafness, the dominant role of elders in household decisions, belief that deafness would resolve, reassurance from a child's overall good health, lack of funds and transportation barriers to reach the centre particularly from rural areas. Parents frequently learned about services through word of mouth. Conclusions : The challenges to accessing appropriate services for deafness operate prior to presentation and include educational, cultural, navigational and financial barriers especially for those of lower socioeconomic status and residents of rural areas. The findings highlighted the need to raise awareness and implement wider screening programmes for early interventions.